Cooking love in Asia: Food, belonging and the making of a multicultural family on Korean film and television. (1st June 2019) - Song, Myoung-Sun
For the last decade, South Korea – a nation that has called itself danil minjok, a phrase that means ethnically homogenous and racially distinctive – has been transitioning from a homogenous country to a multicultural one. This article focuses on the depiction of 'the ethnic female other' in Korean media, more specifically on that of marriage migrants from Southeast Asia. It analyses two Korean media texts, the film Punch (Lee, 2011) and the television programme Love in Asia (2005–15), specifically around scenes depicting food: marriage migrants preparing food, cooking food, eating food, sharing food, etc. How does food function as sociocultural practices in the exploration of migration and the formation of identities for female marriage migrants? This article argues that Korean film and television articulates a rather limited multicultural discourse as part of its national identity, most notably in the depiction of marriage migrants as mothers who are required to actively produce and consume Korean food. In doing so, the article demonstrates that while media depictions of marriage migrants provide a window onto the transitional process of questioning what a 'Korean' family is, it currently remains very limited and ambivalent.